Growth and Yield Potential of Green Pepper as Affected by Nitrogen at Transplanting - Hassan, Siti Aishah; J. M., Gerber; W. E., Splittstoesser (Universiti Putra Malaysia Press, 1993)
Green pepper (Capsicum annuum L. cv. Lady Bell) was grown for 7 weeks and transplanted into the field. The following rates of N were applied: 112, 224, 336 and 448 kg/ha. High N rates at transplanting did not stimulate vegetative growth but suppressed plant growth, particularly during the early growing period. As N rates increased, plants exhibited poor early growth and produced lower early and total fruit yields. Early yield positively correlated with plant dry weight. Doubling the N rate from 112 to 224 kg/ha resulted in a 21% increase in flower buds, but the percentage of fruit set decreased as N rates increased. Fruit set correlated negatively with total leaf N and positively with plant weight, suggesting that a high leaf N content and a lower plant weight were detrimental to fruit set and yield of green pepper.